روايات البارع عن كتاب العين توثيق وموازنة - نجاة خطراوي; منى حامدي (University of El-oued, 2025)
الملخص: لقد تطرقنا في بحثنا هذا إلى "معجم العين" للخليل بن أحمد الفراهيدي، كأقدم المعاجم العربية على الإطلاق ورائد أقدم مدرسة في التأليف المعجمي. كما تناولنا "معجم البارع" لأبي علي القالي ،لأنه من أبرز من تأثروا بـ"العين" في تأليفهم المعجمي. وقد اعتبر بعض الباحثين أن "البارع" يُشبه "العين" إلى حد كبير بسبب كثرة استشهاد القالي بالخليل ونقله عنه، مما يدل على أن علماء الأندلس اعتبروا "العين" المرجع الأساسي في دراساتهم المعجمية. وأردنا اكتشاف علاقات التفاعل و مجالات التأثر بين هذين المعجمين، تحت عنوان "روايات البارع عن كتاب العين توثيق وموازنة". وأخيرا تم التعرض في هذا البحث إلى المواد المعجمية التي نقلها البارع من العين دون تعديل، والمواد التي نقلها بتعديل وتفسير في صياغتها، ثم تلك المواد التي كتبها القالي إلى الخليل ولم نجدها في كتاب العين. Abstract: In this research, we have touched upon the "Al Ain dictionary" by Khalil bin Ahmed al-Farahidi, as the oldest Arabic lexicographer ever and the pioneer of the oldest school of lexical composition. We also dealt with the "lexicon of the adept" by Abu Ali al-Qali, because he is one of the most prominent who were influenced by the"eye" in their lexical composition. Some researchers have considered that "al-Baraa" is very similar to" al-Ayn "due to Al-Qali's frequent quoting and quoting of Hebron, which shows that Al-Andalus scholars considered" al-Ayn " the primary reference in their lexical studies. We wanted to explore the interaction relationships and areas of influence between these two lexicons, under the title "The Master's novels about the book of the eye document and balance". Finally, in this research, we were exposed to the lexical materials that the master transferred from Al-Ain without modification, the materials that he transferred by modification and interpretation in their formulation, and then those materials that Al-Qali wrote to Hebron and we did not find them in the book of Al-Ain.
توثيق وموازنة من البداية الى الغين والفاء والميم
مذكرة .ماستر . لسانيات عامة. 2025
Keywords: معجم البارع – معجم العين – معجم القالي; lexicon of the master – lexicon of the eye – lexicon of the Qali